PERSEPSI GURU TENTANG EFEKTIVITAS PELAYANAN TENAGA ADMINISTRASI SEKOLAH DI SMP NEGERI SE-KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Wahyuli, Wella; Susanti, Lusi; Ermita; Luthfiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the author's observations that indicate the ineffectiveness of administrative staff services in schools. The purpose of this study is to obtain data and information about the effectiveness of school administrative staff services from: 1) program success 2) target success 3) satisfaction with the program 4) input and output levels 5) achievement of overall objectives. This study uses a quantitative descriptive approach. The research population is 175 public junior high school teachers in Bayang District. Meanwhile, the research sample was taken using a simple random sampling technique totaling 65 teachers. The research instrument used is a Likert scale questionnaire with five answer choices that have been tested for validity and reliability. The results of data analysis show that the effectiveness of school administrative staff services from: 1) program success is in the effective category with a respondent achievement rate of 86.48%, 2) target success is in the effective category with a respondent achievement rate of 86.15%, 3) satisfaction with the program is in the effective category with a respondent achievement rate of 87.66%, 4) input and output levels are in the effective category with a respondent achievement rate of 86.84% and 5) achievement of overall objectives is in the effective category with a respondent achievement rate of 86.87%. Based on the results of the study, it can be concluded that the services of school administrative staff in Public Junior High Schools throughout Bayang District have shown effective services.